A social science perspective on screening for Chlamydia trachomatis. Issue 4 (1st August 1999) - Duncan, B; Hart, G
Abstract : A recent report from the chief medical officer's expert advisory group on Chlamydia trachomatis has recommended the setting up of two pilot projects to assess the feasibility of introducing a national chlamydia screening programme. In addition to screening all symptomatic individuals and all attenders at genitourinary medicine clinics, the report recommends opportunistic screening of sexually active young women and women at high risk of infection, who are attending either general practice or family planning clinics. The success of any new screening programme depends on a wide variety of factors, not least the acceptability of such screening to its target population. In recent years, social scientists have made significant contributions to the understanding of the psychological factors which facilitate or inhibit uptake of screening services. The aim of this report is to discuss briefly the contribution social scientists could make to the chlamydia screening programme in the United Kingdom. In particular, the possible effects of screening for a stigmatized condition such as a sexually transmitted infection are explored.